2020
DOI: 10.7717/peerj.9013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of grazing intensities on reproduction patterns of elm trees (Ulmus pumila) in degraded sandy lands in China

Abstract: The effect of grazing on patterns of reproduction in trees has been little reported. We explored the effects of grazing intensities on reproductive growth, allocation patterns, and duration in elm trees (Ulmus pumila L.) at the Horqin Sandy Land, a degraded area in northern China. Current-year shoots were selected from branches and harvested from individual elm trees subjected to one of four grazing intensities (heavy, moderate, light, and no grazing). Shoots, flower buds, flowers, seeds, leaf buds, and leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The reproductive growth extended from February to the beginning of April, whereas the leaves developed throughout April. Tang (2020) observed that the buds of U. pumila trees in a semi‐arid region of North China (119°39′–120°02′E, 42°29′–43°06′N, 480 m a.s.l.) began to expand at the end of March, and that the seed dispersal ended mid‐May.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reproductive growth extended from February to the beginning of April, whereas the leaves developed throughout April. Tang (2020) observed that the buds of U. pumila trees in a semi‐arid region of North China (119°39′–120°02′E, 42°29′–43°06′N, 480 m a.s.l.) began to expand at the end of March, and that the seed dispersal ended mid‐May.…”
Section: Discussionmentioning
confidence: 99%
“…Chen and Xu (2012a,b) studied the extension of Siberian elm growing season as an effect of climate change in China and found that such extension was induced mainly by the advancement of start date of leaf unfolding. In North China, Tang (2020) studied the effect of grazing on the reproductive allocation of U. pumila in woodlands of a semi‐arid region and found that U. pumila trees extended the duration of the reproductive stage under grazing. To the best of our knowledge, phenology according BBCH scale and timing of Siberian elm growth stages have not been reported so far, either the effect of management practices on phenology.…”
Section: Introductionmentioning
confidence: 99%
“…Elm trees provide various ecosystem services and play critical roles in helping to maintain the stability of the ecosystem of sparse woodland. For example, elm trees provide a seed shadow for regeneration and shade for grasses and livestock [15,16].…”
Section: Study Areamentioning
confidence: 99%
“…The seed dispersal process might be influenced by grazing in direct and indirect ways. Directly, grazing promotes more seed production compared with exclosure lands [14,15]. Indirectly, the grazing animals eat and trample vegetation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation